Perception on suctioning techniques towards endotracheal tube among nurses in ICU at Hospital Universiti Sains Malaysia (HospitaL USM) - Hashim, Nor Syuhada Farhanis (Universiti Sains Malaysia, 2013)
A cross-sectional study was conducted to determine the score of perception on suctioning techniques towards endotracheal tube among nurses in ICU of Hospital USM. Samples was taken by randomly sampling among nurses, being critical nurses in intensive care unit (ICU) in Hospital USM (n=40). A constructed questionnaire was used to collect data. Data were analyzed using Statistical for Social Science (SPSS) 20.0 with alpha level of 0.05. Cronbach’s alpha for the questionnaire was 0.701. The participants comprised of 90% diploma in educational level and the rest is 10% degree in educational level among nurses in critical care setting. The finding showed that the score of perception on suctioning technique was very high perception score (47.5%). There were fair correlation (r = 0.428) between the score of perception and nurses’ age. Besides, there were no significant relationship between the score of perception and suctioning technique. In conclusion, nurses’ perception on suctioning technique plays an important role in performing the procedures of ETT suction. Therefore, nurses should also focus on the positive perception as to ensure nurses have positive perception on suctioning technique and the suctioning technique.